Kurganless Cemetery of the Sarmatian Times on the Maloe Storozhevoe Hillfort in the Middle Don Basin - Yuriy D. Razuvaev; Aleksandr N. Merkulov; Sergey A. Nelyubov; Yuliya A. Neretina (Нижневолжский археологический вестник)
The paper publishes research results on five burials discovered at the smaller of the two hillforts of the Scythian era located near the village Storozhevoye 1st on the river Don. The results of their comprehensive archaeological and anthropological study characterize the little-studied kurganless tradition of the Sarmatian period in the forest-steppe Don region. Ethnical, cultural and chronological attribution of the complexes is based on the ritual and material analogies. The study of anthropological materials was carried out using standard methods. Reconstruction of the buried individuals diet was carried out based on the results of the ratio of stable isotopes of nitrogen and carbon (δ13C and δ15N) in bone tissue collagen. The burials were located in the embankment of a shaft and contained the remains of four men (25–30, 25–35, 40–44 and 60+ years old), a teenager (14–19 years old) and a child (5–10 years old). Based on the ritual and a small inventory, they are identified as Sarmatian and dated within the 1st – early 2nd centuries. As a rule, the dead were placed in relatively shallow graves (about 0.4 m) on their backs in an extended position with their heads facing southeast. The two graves destroyed the earlier burials of the teenager and the child, whose skeletal remains were displaced. The burial of an older man stands out buried in a deeper grave (0.7 m) and with a set of objects (an iron dagger, a clay bowl with an iron knife and animal bones). A silver earring and a bone bead were buried with the two individuals. Traces of trauma and pathology on the bones were either absent or few in number (caries, abrasion and loss of teeth). The plant component (apparently millet) dominated the diet of the individuals, but meat and dairy foods occupied an important place as well. The burials apparently belonged to the inhabitants of a hillfort Bol’shoe Storozhevoe located nearby, the layers of which also contain materials from the Sarmatian era. They constituted a small burial ground associated with the lifestyle transformation of one of the semi-nomadic societies in the region.